Accuracy of 3-Dimensional Planning, Implant Templating, and Patient-Specific Instrumentation in Anatomic Total Shoulder Arthroplasty. (6th March 2019) - Iannotti, Joseph P.; Walker, Kyle; Rodriguez, Eric; Patterson, Thomas E.; Jun, Bong-Jae; Ricchetti, Eric T.
Abstract : Background: Use of 3-dimensional (3D) computed tomography (CT) preoperative planning and patient-specific instrumentation has been demonstrated to improve the accuracy of glenoid implant placement in total shoulder arthroplasty (TSA). The purpose of this study was to compare the accuracy of glenoid implant placement in primary TSA among different types of instrumentation used with the 3D CT preoperative planning. Methods: One hundred and seventy-three patients with end-stage glenohumeral arthritis were enrolled in 3 prospective studies evaluating patient-specific instrumentation and 3D preoperative planning. All patients underwent preoperative 3D CT planning to determine optimal glenoid component and guide pin position based on surgeon preference. Patients were placed into 1 of 5 instrument groups used for intraoperative guide pin placement: (1) standard instrumentation, (2) standard instrumentation combined with use of a 3D glenoid bone model containing the guide pin, (3) use of the 3D glenoid bone model combined with single-use patient-specific instrumentation, (4) use of the 3D glenoid bone model combined with reusable patient-specific instrumentation, and (5) use of reusable patient-specific instrumentation with an adjustable, reusable base. Postoperatively, all patients underwent 3D CT to compare actual versus planned glenoid component position. Deviation from the plan (in terms of orientation and location) was compared across groups on the basis of absolute differences and outlier analysis. Univariable and multivariable comparisons were performed. As the initial analyses showed no significant differences in preoperative factors or in deviation from the plan between Groups 1 and 2 or between Groups 4 and 5 across studies, the final analysis was across 3 major treatment groups: standard instrumentation (Groups 1 and 2), single-use patient-specific instrumentation (Group 3), and reusable patient-specific instrumentation (Groups 4 and 5). Results: In nearly all comparisons, there were no significant differences in the deviation from the plan (absolute differences or outlier frequency) for glenoid implant orientation or location across the 3 major treatment groups. Conclusions: This study did not demonstrate that any type of patient-specific instrumentation resulted in consistent differences in accuracy of glenoid implant placement in primary TSA with 3D CT preoperative planning. Surgeons have multiple patient-specific instrumentation options available for improving accuracy of glenoid implant placement when compared with 2D imaging without patient-specific instrumentation. Level of Evidence: TherapeuticLevel II . See Instructions for Authors for a complete description of levels of evidence.